The ecological importance of intraspecific variation. Issue 1 (January 2018) - Des Roches, Simone; Post, David; Turley, Nash; Bailey, Joseph; Hendry, Andrew; Kinnison, Michael; Schweitzer, Jennifer; Palkovacs, Eric
Abstract Human activity is causing wild populations to experience rapid trait change and local extirpation. The resulting effects on intraspecific variation could have substantial consequences for ecological processes and ecosystem services. Although researchers have long acknowledged that variation among species influences the surrounding environment, only recently has evidence accumulated for the ecological importance of variation within species. We conducted a meta-analysis comparing the ecological effects of variation within a species (intraspecific effects) with the effects of replacement or removal of that species (species effects). We evaluated direct and indirect ecological responses, including changes in abundance (or biomass), rates of ecological processes and changes in community composition. Our results show that intraspecific effects are often comparable to, and sometimes stronger than, species effects. Species effects tend to be larger for direct ecological responses (for example, through consumption), whereas intraspecific effects and species effects tend to be similar for indirect responses (for example, through trophic cascades). Intraspecific effects are especially strong when indirect interactions alter community composition. Our results summarize data from the first generation of studies examining the relative ecological effects of intraspecific variation. Our conclusions can help inform the design of future experiments and the formulation of strategies to quantify and conserve biodiversity. A meta-analysis comparing the ecological effects of variation within a species with the effects of species replacement or renewal shows that intraspecific effects may be comparable to, or sometimes stronger than, species effects.